Public lecture by Mr. Dimitar Bozhilov, mayor of Triaditsa district of the Metropolitan municipality, before law students on the topic “The acts of an almost mayor” - Nikolova, Raina (Law Journal of New Bulgarian University, 2022)
The public lecture was devoted to the powers of the district mayor in a municipality. It emphasized on the acts issued by this territorial administrative body. Presents numerous case studies in the fields of civil registration; health, with emphasis gezi during a pandemic situation; education; public works and communal activities; sports and recreation; environmental protection, etc., which the district mayor must resolve in his work.